The site of administration influences both the type and the magnitude of the immune response induced by DNA vaccine electroporation. Issue 28 (22nd June 2015) - Vandermeulen, Gaëlle; Vanvarenberg, Kevin; De Beuckelaer, Ans; De Koker, Stefaan; Lambricht, Laure; Uyttenhove, Catherine; Reschner, Anca; Vanderplasschen, Alain; Grooten, Johan; Préat, Véronique
Abstract: We investigated the influence of the site of administration of DNA vaccine on the induced immune response. DNA vaccines were administered by electroporation at three different sites: tibial cranial muscle, abdominal skin and ear pinna. Aiming to draw general conclusions about DNA vaccine delivery, we successively used several plasmids encoding either luciferase and ovalbumin as models or gp160 and P1A as vaccines against HIV and P815 mastocytoma, respectively. Low levels and duration of luciferase transgene expression were observed after electroporation of the abdominal skin, partly explaining its lower immunogenic performance as compared to the other sites of administration. Analyses of OT-I CD8+ and OT-II CD4+ T cell responses highlighted the differential impact of the delivery site on the elicited immune response. Muscle electroporation induced the strongest humoral immune response and both muscle and ear pinna sites induced cellular immunity against gp160. Ear pinna delivery generated the highest level of CTL responses against P1A but electroporation of muscle and ear pinna were equally efficient in delaying P815 growth and improving mice survival. The present study demonstrated that the site of administration is a key factor to be tested in the development of DNA vaccine.